Strength modulus of elasticity and shrinkage behaviour of POFA concrete - Abdul Awal, A. S. M. (Faculty of Civil Engineering, Universiti Teknologi Malaysia, 2009)
An investigation was carried out to study strength, modulus of elasticity and shrinkage of concrete containing palm oil fuel ash (POFA). Following DoE mix design, OPC concrete was made to have a target mean strength of 50 MPa with 50 ± 5 mm slump. Having the same workability, POFA concrete was prepared where OPC was replaced, mass for mass, by 30% POFA. Laboratory test results based on short-term investigation revealed that the modulus of elasticity of POFA concrete in association with its compressive strength was slightly lower than that of OPC concrete. The measured values of shrinkage, however, demonstrated that the shrinkage strain of POFA concrete was higher than that of OPC concrete. On the basis of shortterm investigation, the one-year shrinkage values of both OPC and POFA concrete were also predicted by extrapolating the data obtained during this period.